Volatilomics Profiling of Counterfeit Perfume by Gas Chromatography Hyphenated to Mass Spectrometry and Fourier-Transformed Infrared Spectroscopy - Hidayah, Siti Nurul; Suma, Artania Adnin Tri; Lukitaningsih, Endang (Indonesian Journal of Chemistry, 2024)
To prevent deleterious effects on consumers and potential health damage caused by counterfeit perfumes, this study aims to distinguish the original perfume from its suspected counterfeit products. Fingerprint and volatilomics profiling was performed using attenuated total reflection-Fourier infrared spectroscopy (ATR-FTIR) and gas chromatography hyphenated to mass spectrometry (GC-MS). Headspace (HS)-GC-MS was optimized to analyze perfume samples containing water. In the presence of water, our optimized HS-GC-MS method shows linalool's consistent signal intensity, providing an alternative analytical method for water-based perfume formulation. The GC-MS chemical characterization revealed 45 compounds detected in the original sample but only four compounds were detected in the counterfeit products: linalool, citronellol, methyl jasmonate, acetic acid, and propanol. This suggests a clear difference in the formulation of counterfeit products. Counterfeit products also cheat by using a lower amount of ingredients. Relative quantification shows that linalool in counterfeit products was as low as only 5.1% of the amount in the original product. In addition, cheaper and hazardous materials like methanol and 6,7-dihydrogeraniol were detected in counterfeit products. The combination of ATR-FTIR, GC-MS, and HS-GC-MS demonstrated fast authentication of counterfeit perfumes for routine quality control purposes and the possibility of water-based perfume analysis.